THE ROLE OF UZBEKISTAN IN THE WORLD ECONOMY AND INTERNATIONAL RELATIONS - Nafisa, Alakhonova (Scientific Impulse, 2023)
This article is about Uzbekistan after independence, mainly in the 21st century. It was written on the topic of the role of the country in the world economy and international relations. In the article, the contribution of the Republic of Uzbekistan to the world economy, import and export its share and role in international relations will be mentioned.